Optimal controllers design for voltage control in Off-grid hybrid power system - Harsha Anantwar; Shanmukha Sundar; B. R. Laksmikantha (Institute of Advanced Engineering and Science, 2019)
Generally, for remote places extension of grid is uneconomical and difficult. Off-grid hybrid power systems (OGHPS) has renewable energy sources integrated with conventional sources. OGHPS is very significant as it is the only source of electric supply for remote areas. OGHPS under study has Induction generator (IG) for wind power generation, Photo-Voltaic source with inverter, Synchronous generator (SG) for Diesel Engine (DE) and load. Over-rated PV-inverter has capacity to supply reactive power. SG of DE has Automatic voltage regulator for excitation control to regulate terminal voltage. Load and IG demands reactive power, causes reactive power imbalance hence voltage fluctuations in OGHPS. To manage reactive power for voltage control, two control structures with Proportional–Integral controller(PI), to control inverter reactive power and SG excitation by automatic voltage regulator are incorporated. Improper tuning of controllers lead to oscillatory and sluggish response. Hence in this test system both controllers need to be tune optimally. This paper proposes novel intelligent computing algorithm , Enhanced Bacterial forging algorithm (EBFA) for optimal reactive power controller for voltage control in OGHPS. Small signal model of OGHPS with proposed controller is tested for different disturbances. simulation results are compared with conventional method , proved the effectiveness of EBFA.